The Population of Young Craters on the Moon: New Catalog and Spatial and Temporal Analysis - Rebecca R. Ghent; Emily S. Costello; A. H. Parker (The Planetary Science Journal, 2024)
We present a new catalog of the Moon’s rayed and rocky craters from 5 to 130 km in diameter. Using data from the Lunar Reconnaissance Orbiter and the JAXA Kaguya/Selene missions, we identify 571 unique craters with albedo, maturity, and/or thermophysical rays, or rocky ejecta, or all of these, located between 70° S and 70° N at all longitudes. We analyze the cumulative size–frequency distribution (CSFD) and spatial distribution of these craters and find that in general the albedo-rayed population and the rocky population are consistent with an aggregate age of ∼1.2 Gyr, and both groups show deviations from the CSFD predicted by canonical production and chronology functions at diameters >30 km. Strikingly, we also find that although the rocky craters and craters with thermophysical rays show uniform spatial distributions with both longitude and latitude, the albedo-rayed craters show a strong equatorial concentration that deviates significantly from uniform and that is too large to be explained by analytical models of orbital motion.